Validation of Metamizole, Thiamin and Pyridoxine Simultaneous Analysis Methods in Tablet Preparations Using HPLC - Vevi Maritha; Lukman Labasy (Alliance oh Health Activists (AloHA), 2018)
The aim of the present study was to develop and validate HPLC method for the simultaneous assay of metamizole, thiamine and pyridoxine in tablet. Metamizole is a substance that is easily hydrolyzed in the precence of water and oxygen. To inhibit the hydrolysis of metamizole during sample preparation prior to HPLC analysis, sodium sulfite is added and its optimum concentration was investigated. The chromatographic system includes a RP C8(2) column (150x4.6 mm, 5 µm particle size) in conjunction with Photo Diode Array (PDA) detector. The optimal chromatographic condition was obtained using a mobile phase consisting of phosphate buffer 35mM pH 3.0: methanol (80:20), flowrate 1.0 ml/min, and 10 µl injection volume. The metamizole, thiamine and pyridoxine were detected at 275 nm and 361 nm for cyanocobalamin. The Hydrolysis of metamizole was successfully inhibited by adding solution containing 1.5 mg/mL sodium sulfite to solvent and 0.5 mg/mL sodium sulfite to mobile phase. The validation results indicate a good specificity and a linear detector responses with r>0.999. The accuracy (% recovery) for metamizole, thiamine and piridoxine were 100.26%; 99.09%; and 100.03%, respectively. The method yields good precision with RSD of metamizole, thiamine and pyridoxine were 2.0912%; 1.4489%; and 0.8418% respectively. In the robustness study, the small changes of mobile phase pH yielded unsymmetrical peaks and lower resolution. The validated method was successfully applied for simultaneous assay of metamizole, thiamine and pyridoxine in tablet. Keywords: validation; metamizole; thiamine; pyridoxine; hydrolysis of metamizole; HPLC